Neem (Azadirachta indica A. Juss; Meliaceae) as the source for plant-based pesticides as an effective and sustainable biocontrol alternative - Tri Eko Wahjono; Agus Suhatman; W. Wihermanto; H. Hadiyanto (BIORE Scientia Publisher, 2024)
The neem tree has strengths such as effective and environmentally friendly active compounds, as well as the ability to improve the quality and productivity of plants organically. However, the use of botanical pesticides has several challenges, such as potentially lower effectiveness compared to chemical insecticides, high production costs, and requiring specific knowledge in formulation and application. Botanical pesticides are readily available tools for insect pest management and are eco-friendly. The research results show that a neem formula at a concentration of 20 ml.l-1 water can cause mortality of brown planthopper is 48.75 - 70%, while mortality in the synthetic insecticide (positive control) at a concentration of 2 ml.l-1 water (as recommended) resulted in 45% mortality. It is obvious that there is a need to develop biological control as alternatives for eco-friendly and sustainable for pests’ control in insect’s pest management strategies. This research study has both qualitative and quantitative approach, data collection strategies were desk review of information and will be based on empirical data and literature. For the desk study, relevant internet web pages were browsed to have an overview of the key concepts of the research issue, problem of pests and diseases control and benefit of neem tree as botanical pesticides. Nevertheless, the use of botanical pesticides can provide long-term benefits to the environment and human health and support more sustainable agriculture. There is a great opportunity for the development of more effective and affordable technology for botanical pesticide production for farmers, but there are also threats such as strong competition from synthetic pesticides. The objective this study aims to determine the potential of neem (Azadirachta indica A.Juss) as a plant producing botanical pesticides as an effective and sustainable biological control alternative.